2019
DOI: 10.3390/foods8120647
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Synthetic Furanones on Listeria monocytogenes Biofilm Formation

Abstract: Furanones are analogues of acylated homoserine lactones with proven antifouling activity in both Gram-positive and Gram-negative bacteria though the interference of various quorum sensing pathways. In an attempt to find new strategies to prevent and control Listeria monocytogenes biofilm formation on stainless steel (SS) surfaces, different concentrations of six synthetic furanones were applied on biofilms formed by strains isolated from food, environmental, and clinical sources grown onto AISI 316 SS coupons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In addition, furanones as green and safe quorum quenchers have been widely used in food preservation and aquaculture disease resistance and did not induce drug resistance. 50 The above results suggest that FN was the most effective and eco-friendly inhibitor for controlling cyanobacterial blooms.…”
Section: Ecotoxicity Evaluationmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, furanones as green and safe quorum quenchers have been widely used in food preservation and aquaculture disease resistance and did not induce drug resistance. 50 The above results suggest that FN was the most effective and eco-friendly inhibitor for controlling cyanobacterial blooms.…”
Section: Ecotoxicity Evaluationmentioning
confidence: 82%
“…For instance, FB produced by Delisea pulchra is the most widely used active substance with a furanone structure for quorum quenching Table summarizes the present application of these molecules as QSIs and as controllers of biofilm formation, motility, and violacein synthesis. At this point, these molecules have not been used to treat cyanobacterial blooms.…”
Section: Resultsmentioning
confidence: 99%
“…De visu analysis of the epifluorescence microscopy images of monospecies L. monocytogenes 48 h biofilms grown on AISI 316 SS revealed a variety of growth on the coupon ( Figure 1 ). Of note, all the L. monocytogenes strains used in the present study were chosen since a previous work demonstrated no statistically significant differences in the level of adhesion in terms of CFU cm –2 ( Rodríguez-López et al, 2019a ). Consequently, differences in the biofilm morphology, such as occupied area, would be attributed to factors other than the amount of viable-and-cultivable cells in the different biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…The list of strains used in this work are included in Table 1. All bacterial species characterized in a previous study from L. monocytogenes-harboring contamination sites located in food industry (Rodríguez-López et al, 2019a).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Improper hygienic conditions and the high resistance of biofilms formed on surfaces of food processing environments are considered the main causes of L. monocytogenes increases the probability of food contamination (Mazaheri et al, 2021). Several studies have shown that L. monocytogenes survives in food processing facilities by forming or integrating into multispecies microbial communities at contamination sites (Galié et al, 2018;Rodríguez-López et al, 2019a). Moreover, even after cleaning and disinfection, L. monocytogenes-containing polymicrobial biofilms have been detected (Carpentier and Chassaing, 2004;Rodríguez-López et al, 2015).…”
Section: Introductionmentioning
confidence: 99%